2011
DOI: 10.1016/j.bbamcr.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Karyopherins in nuclear transport of homeodomain proteins during development

Abstract: Homeodomain proteins are crucial transcription factors for cell differentiation, cell proliferation and organ development. Interestingly, their homeodomain signature structure is important for both their DNA-binding and their nucleocytoplasmic trafficking. The accurate nucleocytoplasmic distribution of these proteins is essential for their functions. We summarize information on a) the roles of karyopherins for import and export of homeoproteins, b) the regulation of their nuclear transport during development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 145 publications
0
15
0
Order By: Relevance
“…However, in our IHC analysis, we detected PITX2 signaling in the cytoplasm in both ESCC and adjacent non‐neoplastic tissues, although at different levels. By reviewing the literature, we found that altered intracellular localization of PITX2 is not uncommon, either because of destabilization of the homeodomain or a result of loss of potential nuclear localization signal 44, 45. For example, in Murine C2C12 myoblasts, PITX2 displays a predominant cytoplasmic localization and is necessary to ensure proper cellular proliferation and differentiation 46.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our IHC analysis, we detected PITX2 signaling in the cytoplasm in both ESCC and adjacent non‐neoplastic tissues, although at different levels. By reviewing the literature, we found that altered intracellular localization of PITX2 is not uncommon, either because of destabilization of the homeodomain or a result of loss of potential nuclear localization signal 44, 45. For example, in Murine C2C12 myoblasts, PITX2 displays a predominant cytoplasmic localization and is necessary to ensure proper cellular proliferation and differentiation 46.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the practical utility of Q‐SCAn to examine a classical signaling paradigm for multicompartment protein localization, the movement of a transcription factor from the cytoplasm to the nucleus , we analyzed the localization of the S. cerevisiae transcription factor, Yap1 . Under normal cellular conditions, Yap1 shuttles between the nucleus and the cytoplasm but shows diffuse, steady‐state localization primarily to the cytoplasm, as the rate of nuclear export exceeds the rate of nuclear import .…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, their HD signature structure is important for both their DNA binding ability and their nucleocytoplasmic trafficking [14]. The accurate nucleocytoplasmic distribution of these proteins is essential for their functioning [15].…”
Section: Discussionmentioning
confidence: 99%